2021
DOI: 10.1029/2021gc009823
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of Slab Tracers, Volatiles, and Oxidation During Subduction Initiation

Abstract: Subduction‐related lavas have higher Fe3+/∑Fe than midocean ridge basalts (MORB). Hypotheses for this offset include imprint from subducting slabs and differentiation in thickened crust. These ideas are readily tested through examination of the time‐dependent evolution of slab‐derived signatures, thickening crust of the overriding plate, and evolving redox during subduction initiation. Here, we present Fe3+/ΣFe and volatile element abundances of volcanic glasses recovered from International Ocean Discovery Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 94 publications
(248 reference statements)
0
17
0
Order By: Relevance
“…In the early stage, the IBM arc was aligned east-west near the equator; however, it gradually rotated to a north-south alignment and migrated northward (Hall, 2002;Taylor & Goodliffe, 2004). Recent studies revealed that the volcanism in the early stage was characterized by forearc basalt at 52.5 Ma, and boninite for the infant arc edifice building at 51.3-46 Ma (Arculus et al, 2015;Brandl et al, 2017;Brounce et al, 2021;Ishizuka, Tani, et al, 2011, Ishizuka et al, 2018Robertson et al, 2018), followed by the mature arc edifice building (40-28 Ma;Brandl et al, 2017;Johnson et al, 2021). In particular, the volcanism in the latest Eocene to early Oligocene (∼37-28 Ma) was dominated by subaerial and subaqueous explosive volcanism producing the vitric ash, accompanied by the growth of the initial Izu-Bonin-Mariana arc, including the section called the Kyushu-Palau Ridge (KPR;Shipboard Scientific Party, 2002;Johnson et al, 2021).…”
Section: Geological and Sedimentological Backgroundmentioning
confidence: 99%
“…In the early stage, the IBM arc was aligned east-west near the equator; however, it gradually rotated to a north-south alignment and migrated northward (Hall, 2002;Taylor & Goodliffe, 2004). Recent studies revealed that the volcanism in the early stage was characterized by forearc basalt at 52.5 Ma, and boninite for the infant arc edifice building at 51.3-46 Ma (Arculus et al, 2015;Brandl et al, 2017;Brounce et al, 2021;Ishizuka, Tani, et al, 2011, Ishizuka et al, 2018Robertson et al, 2018), followed by the mature arc edifice building (40-28 Ma;Brandl et al, 2017;Johnson et al, 2021). In particular, the volcanism in the latest Eocene to early Oligocene (∼37-28 Ma) was dominated by subaerial and subaqueous explosive volcanism producing the vitric ash, accompanied by the growth of the initial Izu-Bonin-Mariana arc, including the section called the Kyushu-Palau Ridge (KPR;Shipboard Scientific Party, 2002;Johnson et al, 2021).…”
Section: Geological and Sedimentological Backgroundmentioning
confidence: 99%
“…The f O 2 value and the timescale of the IBM forearc is after Brounce et al. (2015, 2021) and Ishizuka et al. (2011), respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, such secondary processes might not account for the high fO 2 values of the IBM proto-arc boninites. Indeed, Brounce et al (2021) estimated that the fO 2 of the IBM boninitic magmas may have decreased by ∼0.5 orders of magnitude if sulfur was lost to the gas phase, and so the calculated fO 2 values would only represent minimum estimates. Therefore, S degassing as well as other shallow-level processes would not account for the high fO 2 values of the IBM boninites (Brounce et al, 2021).…”
Section: Possible Reasons For the Different Oxidation State Between T...mentioning
confidence: 99%
“…Indeed, despite being primarily classified as highly siderophile, PGE also have a strong affinity for S 2− dissolved in silicate melts (Laurenz et al, 2013) or in sulfide liquids (Mungall and Brenan, 2014). Since Hamlyn and Keays (1986), technical progress has allowed the analyses of chalcophile and highly siderophile trace elements with greater accuracy and precision in boninites, further supporting that these magmas are undersaturated in sulfide at relatively low-P conditions (e.g., on the ocean floor; Woodland et al, 2002;Dale et al, 2012;Valetich et al, 2019;Brounce et al, 2021). However, neither PPGE enrichments nor sulfide undersaturation are specific to boninites under these low-P conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies of sub-arc mantle peridotites have shown that both HCB and LCB endmember can be characterized by high volatile contents and an elevated oxidation state at a primitive stage (Bénard et al, 2016;Bénard et al, 2017b;Bénard et al, 2018b;Bénard et al, 2018c;Bénard et al, 2022). However, large variations in volatile contents and oxidation state are sometimes observed in boninites sampled on the ocean floor, even though they are not as primitive as those in mantle peridotites (Brounce et al, 2015;Brounce et al, 2021).…”
Section: Introductionmentioning
confidence: 99%